Swimming performances in long distance open-water events with and without wetsuit - Ulsamer, S.; Rüst, C.; Rosemann, T.; Lepers, R.; Knechtle, B. (BMC Sports Science, Medicine and Rehabilitation, 2014)
Existing literature showed improved swimming performances for swimmers wearing wetsuits competing under standardized conditions in races held in pools on short to middle distances. Data about the influence of wetsuits on swimming performances in long and ultra-long open-water swimming races are missing. It is unknown whether the benefit of wearing wetsuits is comparable in men and women. The aim of this study was to investigate the influence of wearing a wetsuit on open-water swimming performances at the 26.4 km `Marathon Swim in Lake Zurich` in Lake Zurich, Switzerland, and the 3.8 km Lake Ontario Swim Team-Race (LOST-Race) in Lake Ontario, Canada.